"It's not just a picture": The effects of an international two-week field experience on student geoscience involvement and persistence. Issue 3 (3rd July 2022) - Boyd, Evelyn Abagayle; Lazar, Kelly Best
Abstract: Recruitment and retention are critical for geoscience and the need for innovative ways of building these bridges to the geosciences is growing. Field experiences are a common attractor for students to the field sciences such as geoscience, but many research- and field-based experiences are limited to those who are already majors. Innovative, experiential approaches to geoscience recruitment and retention could be a new way to attract more students to geoscience. International field and research experiences designed for undergraduates from any academic discipline aim to provide opportunities for students to explore their (geo)science interests and potential career paths. A single, exploratory case study approach with semi-structured interviews combined with quantitative pre- and post-survey results is used to highlight the experiences of four students and their plans for continuing in the geosciences. Students (including geoscience and non-geoscience majors) were found to have had inherent, pre-college, and college influences for participation in the field experience; all students indicated plans to continue in the geosciences. Two years after the experience, researchers followed-up with the students and found that three of the four were still involved in the geosciences. Many international geoscience field experiences are exclusively for majors, but experiential learning opportunities like these should also be considered for potential majors. These results are beneficial for departments interested in designing and adapting their recruitment and retention efforts to better train the next generation of geoscientists.